The Relationship of Diabetic Macular Edema andProliferative Diabetic Retinopathy with CardiovascularEvents in Patients with Type 2 Diabetes Mellitus: A Comperhensive Systematic Review - Lianda, Felia; Priyanto, Tri Hendro (International Medical Journal Corp. Ltd, 2024)
Background: Diabetic retinopathy (DR) is the most frequent microvascular complication of diabetes mellitus, affecting up to one-third of all individualswith the disease. DR can lead diabetic macular edema (DME). Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Conclusion: The association between the increased burden of proliferative retinopathy and the occurrence of heart failure in patients with diabetes who are at a high risk of CVD morbidity and mortality.